PENGARUH PENERAPAN BUDAYA ORGANISASI DAN PEMBERIAN KOMPENSASI FINANSIAL LANGSUNG TERHADAP KEPUASAN KERJA KARYAWAN - Herlina Herlina; Heri Sasono (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine the effect of organizational culture (X1) and direct financial compensation (X2) on employee job satisfaction (Y). This research is a quantitative approach by performing parametric statistical analysis in the form of multiple linear regression analysis. The population in this study were 207 employees and a sample of 52 respondents using the Nonprobability Sampling technique. Data collection techniques using a questionnaire. The data was processed using SPSS (Statistics of Package for the Social Sciences) version 22 for window. The results showed that partially variable X1 and Variable X2 had significant effect on variable Y. Meanwhile, simultaneously, organizational culture and financial compensation had a positive and significant effect on job satisfaction and the determinant coefficient was 69.6%.